The Bible As A Green Text? - Lipowski, Paul M. (European Scientific Journal, ESJ, 2016)
With an increasing debate over human impact on the environment, can we look at how the environment can be treated through a Christian perspective? Pope Francis, in the Roman Catholic tradition, has paved the way with Laudato Si and given much to think about. Is the Bible fundamentally a ‘Green’ text? Have people been misinterpreting the message on how to care for the environment? This essay will examine what theologians have said in regards to the Bible and the environment and conclude that in the Bible we can find it to be a ‘Green’ text.